Development Of A Solid – Based Paper Strip Assay For Rapid Diagnosis Of Pseudorabies - Tam, Yew Joon (2004)

(untitled)
Pseudorabies (Aujeszky’s disease) is an economically significant disease of swine known to cause central nervous disorders, respiratory disease, reproductive failure and mortality in infected pigs. In attempts to eradicate the disease from becoming endemic, early detection is important to prevent further economic losses and to allow for detection and removal of infected pigs in domestic herds. Thus, a rapid and sensitive technique is necessary for the detection of the virus. For rapid and simple examination, an immuno – chromatographic lateral – flow assay system based on immunologic recognition of specific pseudorabies virus antigen was developed by utilising, as signal generator, colloidal gold conjugated to secondary antibody to detect primary or sample antibody in the sera of pseudorabies infected animals. The pseudorabies virus used as a capture antigen in the test strip was first cultivated in VERO cell culture and then purified by sucrose gradient separation to produce the viral protein concentration of 3.8 mg/ml. A sample of the antigen stock was then subjected to SDS PAGE protein analysis. Minor differences were noted between the sample proteins and reported protein profile of pseudorabies virus. The standard pseudorabies antigens reacted well with the hyperimmune serum (HIS). The antibody detection system is basically composed of colloidal gold – labelled antibodies fixed on a conjugate pad, and the complementary pseudorabies antigen immobilised onto a nitrocellulose membrane forming capture zone. If the target antibody is present in a specimen, the colloidal gold-labelled antibody will form a complex with the antibody sample. Subsequently, the formed complex will migrate to the capture zone and is then bound to the solid phase via antigen – antibody interaction. As a result, a signal marker is generated by the accumulation of colloidal gold for detection confirmation. The results obtained demonstrated that the optimum combination of pseudorabies antigen needed as the capture reagent and gold conjugate as secondary antibody recognition marker was at a concentration of 0.38mg/ml and at 1:10 dilution factor respectively. The sensitivity of the solid – based test strip towards pseudorabies antibodies was high with a detection limit of 1 to 10,000 – dilution factor. The specificity of the assay was 100% with no cross – reaction being observed with other sera or antibodies. Accurate reading time needed for confirmation of the assay can be completed in 5 min with a whole blood sample of 25 μl. The colloidal gold – labelled antibody is stable at room temperature for 6 months or more. Findings from this study indicated that the solid – based test strip assay system provided high sensitivity and specificity for the detection of pseudorabies at low levels of antibody concentration. The assay was rapid, simple, cheap, and does not require any sophisticated equipment. Thus, the solid based test strip will be a useful serological screening technique or for rapid diagnosis of an infectious disease in target populations of animals characterised by heterogeneous antibody responses.